An operating room audit to examine for patterns of staff entry/exit: pattern sequencing as a method of traffic reduction - Anderson, Rachel L (J Infect Prev, 2020)
BACKGROUND: Surgical site infections (SSIs) are estimated at over 16,000 annually and cost hospitals an estimated $1.6 billion per year. Therefore, most operating rooms (ORs) seek methods to reduce the risk of SSI, especially during the intraoperative period. Prior work has established a link between excess traffic through the OR and increased microbial counts, which create a higher risk for SSIs. AIM/OBJECTIVES: To identify patterns of staff entry into the OR to further reduce the risk of SSIs after total joint arthroplasties. METHODS: Researchers directly observed 31 total joint arthroplasties, recording every instance the door to the OR suite opened and the personnel, reason for opening and timing during surgical incision. Researchers then utilised the sequential data analysis to search for patterns. RESULTS: Despite expected patterns in staff movement during the patterned surgery, researchers found no significant patterns to staff movement during total joint arthroplasty. DISCUSSION: This study’s results suggest purposeful education targeted to circulating registered nurses could induce purposeful creation of traffic flow patterns to further decrease traffic and risk of SSI. CONCLUSION: There is no singular pattern to entering and exiting the OR during surgery. Thus, a single-solution approach is not recommended.